Distal transposition of rat caecum does not render it susceptible to carcinogenesis. Issue 7 (July 1985) - Rainey, J B; Maeda, M; Williamson, R C
Abstract : As the relative resistance of rat caecum to chemical carcinogens could reflect its luminal environment, caecal mucosa was exposed to the distal faecal stream in male Sprague-Dawley rats (n = 50) previously treated with azoxymethane (total dose 90 mg/kg sc). After colonic transection at the pelvic brim, the caecum was inserted isoperistaltically between colocaecal and caecorectal anastomoses (n = 30); an ileocolic anastomosis restored intestinal continuity. Controls (n = 20) had transection and reanastomosis at equivalent points of the bowel, plus caecotomy and resuture. Caecal crypt cell production rate, as determined stathmokinetically at 28 weeks, was not consistently affected by transposition. No tumors developed in either transposed or orthotopic caecum, apart from three suture-line tumours found at the caecotomy site in controls. The colonic tumour yield in controls (1.4 +/- 0.3 per rat : mean +/- SEM) matched that after transposition (1.5 +/- 0.2), but anastomotic tumours were twice as common after transposition (p less than 0.05) and rectal tumours were increased four-fold (p less than 0.05). The caecum remains resistant to carcinogenesis despite transposition to a distal colonic environment. Local epithelial defence mechanisms are more important than luminal contents in maintaining this resistance.